THE PRACTICE OF HYDROTHERAPY IN THE NORTH CAUCASUS OF THE GOLDEN HORDE AGE - Abzalov, Lenar Firgatovic (History, Archeology and Ethnography of the Caucasus, 2020)
Basing on brief information of Arabic sources, the author attempts to analyze the practice of hydrotherapy in the territory of the modern Caucasian Mineralnye Vody, which was part of the Golden Horde during the period under consideration. The aim of the article is the characteristic of the practice of hydrotherapy in the said region by the figures of the Golden Horde elite. The research methodology is based on the historical-comparative method, the method of retrospective analysis, applied on the basis of an interdisciplinary approach. The analysis of brief messages of Ibn Battuta allows for conclusion that hydrotherapy was practiced in the Golden Horde, and the healing properties of mineral waters of the North Caucasus were widely used. Hydrotherapeutic procedures were carried out according to certain regulations, which had been designed both empirically and theoretically on the basis of works of prominent physicians. Water procedures in the Golden Horde were not only known, but also actively practiced to treat various diseases and quite possibly being more common than it was generally believed. It is worth noting that almost every region of the Golden Horde had its own healing and mineral springs, and every nation had its own views on water, health and healthy lifestyle, which in turn determined the special methods of hydrotherapy; however, for a number of objective reasons, hydro- and balneotherapy were widely spread mostly in the Caucasian region of Mineralnye Vody.